Educational Management Strategy for Literary Reading Materials through the Novel Nadira by Leila S. Chudori for Eleventh Grade Students - Rahmita; Muhamad Burhanuddin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
The problem of literature learning in Grade XI senior high schools is related to students’ low interest in reading and the difficulty of understanding novels with complex language and narrative structures. This study examines the simplification of the novel Nadira by Leila S. Chudori as an alternative literary reading material using Seymour Chatman’s narrative structuralism theory. The results indicate that simplification can be carried out by simplifying the language and textual structure without eliminating the theme, plot, characters, conflicts, and aesthetic values. Consequently, the resulting teaching material is easier to understand and more suitable for Grade XI students.